Structural Controls on Aftershock Distribution in Subduction Zones - Richards, Simon (Frontiers in Earth Science, 2020)
The trench-parallel distribution of aftershocks generated after a major subduction-related earthquake does not conform to a fractal or normal distribution as expected but does appear to be spatially constrained by fractures on the subducting oceanic crust. Newly developed and very detailed 3D models of subducting plates (slabs) are combined with high-resolution topographic and bathymetric models of the crustal upper-plate and subducting lower-plate respectively to show how irregularities such as transform faults, spreading centers, fossil subduction zones and vertical tears form structural barriers to the spatial distribution of subduction zone aftershocks. When correctly constructed, slab models can now be used to better forecast the lateral (along-arc) extent of damaging aftershock swarms following large magnitude subduction-related earthquakes. Two earthquakes, (magnitude MW 7.8 in Vanuatu, 7th October 2009 (UTC) and magnitude MW 8.8 in southern Chile, 27th February 2010 (UTC)) were followed by hundreds of aftershocks, with many recording magnitudes over MW 6.5. Closer examination of these aftershocks and their spatial distribution indicate that they were unexpectedly confined to discrete sections of the subducting plate. It is revealed here that lithospheric-scale structures including fossil oceanic transform faults represent crustal and lithosphere-scale fractures in the crust that terminates the lateral spread of aftershocks. This contrasts with the predicted decrease in aftershock size and number with increasing distance from the epicenter referred to as the Omori (power law) distribution. This hypothesis addresses the paradigm that oceanic crust is a single, semi-continuous and uniform section of crust where the lateral distribution of earthquakes is described in terms of uniform rock mechanics. Additional research on the MW 9.0 earthquake in Japan (11th March 2011 (UTC)) and the MW 8.0 earthquake in the eastern Solomon Islands (6th February 2013 (UTC)) supports the aforementioned hypothesis. Using new techniques to help define the location of sub-plate boundaries, it is now possible to generate aftershock probability maps for some of the most seismically active subduction margins around the world.